International Evidence on Sticky Consumption Growth - Carroll, Christopher D.; Slacalek, Jiri; Sommer, Martin (The Review of Economics and Statistics, 2011)
This paper estimates the degree of stickiness in aggregate consumption growth (sometimes interpreted as reflecting consumption habits) for thirteen advanced economies. We find that after controlling for measurement error, consumption growth has a high degree of autocorrelation, with a stickiness parameter of about 0.7 on average across countries. The sticky consumption growth model outperforms the random walk model of Hall (1978) and typically fits the data better than the popular Mankiw (1989) model, though in a few countries, the sticky consumption growth and Campbell-Mankiw models work about equally well.